Modelling real choice between conventional ad electric cars for homebased journeys - Jensen, Anders Fjendbo; Mabit, Stefan Lindhard (Proceedings from the Annual Transport Conference at Aalborg University, 2015)
Over the last decades, several studies have focused on understanding what drives the demand for electric vehicles (EVs) and to what extent the difference in several characteristics – especially the limited driving range and limited charging options - makes it a feasible transport alternative compared to conventional internal combustion engine vehicles (ICVs). However such studies do not reveal to what extent households would actually use an EV for travel if they had the choice. We utilize a dataset describing household travel with either a private ICV or an EV that was available to the household for three months in connection with a large-scale EV demonstration project in Denmark. These data allow us to study what factors that influence the choice between an EV and an ICV for home-based journeys. The results show that several factors related to the time, length and number of trip legs affect the choice of the EV. Furthermore, we show that whether it is necessary to recharge the battery during the journey as well as the weather at the time of departure has an effec